Genetic diversity of the criollo horse (Equus caballus) by genes associated to the skin coat in Valencia, Colombia - Yepes, Wilson (2017)
The objective of this study was to investigate the genetic variability of criollo horses (Equus caballus) by genes associated with the coat. Fields visits were done between January and May 2016 in five populations of the municipality of Valencia, Colombia. The phenotypic characterization of the adult animals present in the farms was performed in relation to the autosomal markers of morphological codification Extension, Agouti, Cream, Gris, White, Tobiano, Overo and Roan. The results showed absence of the markers White and Overo, whereas the markers Extension and Agouti had the largest frequencies, possibly favored by artificial selection due to temperament and cunning respectively. Populations were found in equilibrium Hardy-Weinberg and showed excess of homozygotes and high levels of gene flow.